2019
DOI: 10.1002/pbc.27648
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma incidence among children and adolescents in Texas and SEER 13, 1995–2013

Abstract: Background Epidemiological knowledge and predictors of melanoma among children and adolescents in multiethnic populations are limited. Procedure Using data from the Texas Cancer Registry (TCR) and the Surveillance, Epidemiology, and End Results (SEER) 13 database, we identified incident melanoma cases diagnosed at 0–20 years old during 1995–2013 in Texas and the United States, respectively. Using negative binomial regression, associations between demographic factors and melanoma incidence rates (IR) were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
(47 reference statements)
5
13
1
Order By: Relevance
“…Similar trends have been observed in previous studies. 2,5,8,[12][13][14][15][16] However, our results differ from a previous international cancer registry analysis which found that males made up a greater percentage of cases before the age of 10, while females made up a greater percentage of cases after the age of 10. 8,13 Our results demonstrated a greater burden of melanoma in males age 13-15 and females age 16-17.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar trends have been observed in previous studies. 2,5,8,[12][13][14][15][16] However, our results differ from a previous international cancer registry analysis which found that males made up a greater percentage of cases before the age of 10, while females made up a greater percentage of cases after the age of 10. 8,13 Our results demonstrated a greater burden of melanoma in males age 13-15 and females age 16-17.…”
Section: Discussioncontrasting
confidence: 99%
“…We also observed several cases at age 0‐12 months. However, melanoma in this age group has been observed in previous studies 1,2,12,15,17,18 …”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Five articles reported disparities in pediatric skin cancer, specifically melanoma. Among non-White minorities, a higher incidence of melanoma in Hispanics was found by Danysh et al 37 using the Surveillance, Epidemiology, and End Results (SEER) 13 database. Hispanics were also found to present with later-stage disease and have lower survival rates.…”
Section: S K In C An Cermentioning
confidence: 87%